Electromagnetic Analysis of Different Materials for High Temparature Machine - F.Zainuddin, M.; Aziz, R.; Ahmad, Zarafi (International Journal of Engineering and Technology, 2018)
Permanent magnet synchronous motor (PMSM) consist of permanent magnet at the rotor to produce a constant magnetic field. Permanent magnet synchronous motor (PMSM) classified into two categories which is Interior Permanent Magnet Synchronous Motor (IPMSM), and Surface Permanent Magnet Synchronous Motor (SPMSM). For IPMSMs, permanent magnet is embedded inside the rotor core while for SPMSMs, the permanent magnet is attached at the surface of the rotor. IPMSMs offers high torque and power density. However, it produce high cogging torque compared to SPMSMs. The performances of IPMSMs also related to the permanent magnet materials that used to produce constant magnetic flux for the motor. In this research, design study of 8 pole 12 slot, V-shaped permanent magnet with various rotor topology is studied to compare the performances with different permanent magnet materials. The permanent magnet materials that have been selected are Neodymium-Iron Boron (NdFeB), AlNiCo, and Samarium-Cobalt (SmCo). Initially, design procedures of IPMSM including parts drawing, material and condition setting, the properties setting are all explained. Then, coil arrangement test is conducted to perform 3 phase armature coil arrangement. Then, no load analysis is conducted to analyse cogging torque, flux linkage, flux distribution and back-EMF of motor followed by load analysis which analyse the torque speed characteristics, output power, and efficiency of the motor with different permanent magnet materials. No load analysis and load analysis is conducted using finite element analysis of JMAG Designer 14.0. Finally, it is found that the best permanent magnet material for IPMSM is NdFeB due to the capability to produce high output torque and efficiency based on the analysis conducted.Â